1998
DOI: 10.1269/jrr.39.1
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of p53 Overexpression in Radiation-Induced Colon Cancers.

Abstract: The expressions of p53 and proliferating cell nuclear antigen (PCNA) were studied immunohistochemically from paraffin sections of 7 cases (9 lesions) of radiation-induced colon cancer and 42 cases of spontaneous colon cancer. Age distribution of radiation-induced and spontaneous colon cancer were 68.1 years (range, 56 to 77 years) and 67.4 years (range, 31 to 85 years), respectively. Among the radiation-induced colon cancers, there were 3 lesions of mucinous carcinoma (33%), a much higher than found for sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In the present case, there was no detected hereditary tendency for malignancy, and there was no MSI, although the first flat tumor harbored a p53 mutation. Similar to the present case, Minami et al (17) reported that p53 protein overexpression was detected using immunohistochemistry in 7 of 9 patients with radiation-associated colon cancer; however, they found no definite correlation between the overexpression of p53 in radiation-associated and spontaneous colon cancers. This suggested that the occurrence of p53 gene mutations was not specific to the carcinogenesis of radiation-associated colon cancers compared with spontaneous colon cancers.…”
Section: Discussionsupporting
confidence: 82%
“…In the present case, there was no detected hereditary tendency for malignancy, and there was no MSI, although the first flat tumor harbored a p53 mutation. Similar to the present case, Minami et al (17) reported that p53 protein overexpression was detected using immunohistochemistry in 7 of 9 patients with radiation-associated colon cancer; however, they found no definite correlation between the overexpression of p53 in radiation-associated and spontaneous colon cancers. This suggested that the occurrence of p53 gene mutations was not specific to the carcinogenesis of radiation-associated colon cancers compared with spontaneous colon cancers.…”
Section: Discussionsupporting
confidence: 82%
“…Besides, in radiation colitis involving aberrant glands, cellular proliferation increases and spotted oncogene p53 expression is noticed. Therefore, radiation colitis and aberrant glands with p53 overexpression might predict malignant potential of this condition [37] . Three typical phases of radiation proctitis are defined on histological grounds (acute damage, and early and late regenerative phases), essentially correlating with the time interval between radiotherapy and surgery.…”
Section: Chronic Radiation Colitis (Table 2)mentioning
confidence: 99%
“…Radiation-induced colitis may be encountered as one of the most harmful side-effects of radiation therapy for pelvic malignancies 1) . During the treatment of these malignancies with external, intracavitary, or combined irradiation, the rectum often receives a substantial expo-…”
Section: Introductionmentioning
confidence: 99%